Re-description of the gudgeon species Saurogobio gracilicaudatus Yao & Yang in Luo, Yue & Chen, 1977 (Teleostei: Cyprinidae) from the Chang-Jiang basin, South China, with a note on its generic classification - Dai, Zhen-Yan; Zhang, E; Jiang, Zhong-Guan; Wang, Xue (Zootaxa, 2014)
Saurogobio gracilicaudatus, originally described from the middle Yangtze River (Chang-Jiang in Chinese) basin at Yichang and Guanghua (now Laohekou), Hubei Province, South China, is here re-described, with particular concern for oromandibular structures in the mouth. It is uniquely distinguishable from all other species of Saurogobio in having a rostral cap with a slightly crenulated median portion, lips covered with brush-like, conical papillae, and a lower lip with a small, smooth and protruded central pad anteriorly free and posteriorly confluent with lateral lobes. The generic classification of this species is also discussed on the basis of oromandibular structures, which are of taxonomic importance in generic classification of gudgeons.